The Era of Prophet Muhammad (Prophet's Period in Mecca) - Wan Mai Zulia; Ismail Marzuki; Selamat (Yayasan Tahfidzul Qur'an Al-Fawwaz, 2024)
This research is motivated by the era of Prophet Muhammad SAW in Mecca, a crucial phase in Islamic history marked by a challenging and arduous mission of dawah. The aim is to understand the dynamics of Prophet Muhammad's dawah in Mecca, including the strategies employed, the challenges faced, and the impact it had. Employing historical qualitative research with a content analysis approach on primary sources like the Quran and Hadith, and secondary sources such as historical books and biographies, the study involves literature studies and descriptive analytical methods for data analysis. Data validation is conducted through source triangulation. Findings reveal that Prophet Muhammad's dawah in Mecca focused on spreading monotheism and instilling Islamic faith amidst a society that worshipped idols, marked by rejection and persecution from the Quraysh. Despite numerous obstacles, this dawah laid a strong foundation for Islam and fostered a resilient Muslim community. The research's novelty lies in its in-depth analysis of the dawah strategies and the Meccan society's response, along with its contemporary relevance, recommending further exploration of specific dawah aspects like the role of the Prophet's companions.